Exosomal biomarkers in leukemia: translational potential and regulatory challenges for precision medicine applications - Ansarian, Mohammad Amin; Fatahichegeni, Mahsa; Wang, Yuqi; Ren, Juan; Zhang, Tongxin; Wang, Xiaoning (Frontiers in Immunology, 2025)
Exosomes represent a paradigm shift in leukemia biomarker research, evolving from overlooked cellular waste products to sophisticated intercellular messengers with significant clinical implications for hematological malignancies. These membrane-bound vesicles carry disease-specific molecular cargo, including proteins, lipids, and nucleic acids that mirror leukemic cell pathology, making them accessible through minimally invasive liquid biopsies. Current evidence demonstrates characteristic molecular signatures across different leukemia subtypes, with exosomal microRNAs such as miR-150, miR-155, and the miR-29 family showing diagnostic and prognostic value, while protein markers including CD19, CD20, and IFITM3 correlate with disease status and therapeutic responses. Beyond diagnostic applications, exosomes orchestrate complex biological processes that reshape the bone marrow microenvironment, facilitate immune evasion, and promote treatment resistance through intercellular molecular exchange, presenting both challenges and therapeutic opportunities. Clinical translation has gained momentum through European regulatory frameworks, with exosomes classified as advanced therapy medicinal products under EMA guidelines. Early clinical trials demonstrate safety and feasibility, while diagnostic precedents like the ExoDx Prostate Test provide regulatory pathways for implementation. However, significant obstacles persist, including standardization of isolation methods, validation of biomarker panels, and integration with existing clinical decision algorithms. European collaborative initiatives through organizations like ISEV-ELBS and the HARMONY consortium address these challenges by establishing standardized protocols and conducting multi-center validation studies. The integration of artificial intelligence and machine learning approaches offers transformative potential for addressing clinical implementation challenges, with algorithms demonstrating superior discrimination capabilities and standardization solutions. While most exosomal biomarkers remain in early validation phases requiring comprehensive clinical development, the convergence of advancing analytical technologies, evolving regulatory frameworks, and collaborative research initiatives positions exosomes as promising tools for advancing precision medicine in leukemia. However, realistic timelines and sustained investment in methodological standardization remain essential for successful clinical translation.